Tolerability of BRAF/MEK inhibitor combinations: Adverse event evaluation and management - Heinzerling, Lucie; Eigentler, Thomas K.; Fluck, Michael; Hassel, Jessica C.; Heller-Schenck, Daniela; Leipe, Jan; Pauschinger, Mathias; Vogel, Arndt; Zimmer, Lisa; Gutzmer, Ralf (ESMO Open, 2019)
The inhibition of the mitogen-activated protein kinases signalling pathway through combined use of BRAF and MEK inhibitors (BRAFi+MEKi) represents an established therapeutic option in patients with BRAF-mutated, advanced melanoma. These efficient therapies are well tolerated with mostly moderate and reversible side effects and a discontinuation rate due to adverse events of 11.5%-15.7%. Median duration of therapy ranges between 8.8 and 11.7 months. Based on data from confirmatory trials, safety profiles of three BRAFi+MEKi combinations were reviewed, that is, dabrafenib plus trametinib, vemurafenib plus cobimetinib and encorafenib plus binimetinib. Many adverse events are class effects, such as cutaneous, gastrointestinal, ocular, cardiac and musculoskeletal events; some adverse events are substance associated. Fever (dabrafenib) and photosensitivity (vemurafenib) are the most common and clinically prominent examples. Other adverse events are less frequent and the association to one substance is less strong such as anaemia, facial paresis (encorafenib), neutropenia (dabrafenib), skin rash, QTc prolongation and increased liver function tests (vemurafenib). This narrative review provides recommendations for monitoring, adverse event evaluation and management focusing on the clinically relevant side effects of the three regimens.
CRIS-Team Scopus Importer:2019-06-04
Keywords: adverse events; BRAF; MEK; melanoma; safety